2013
DOI: 10.3163/1536-5050.101.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Faculty experiences with the National Institutes of Health (NIH) public access policy, compliance issues, and copyright practices

Abstract: There is a need to educate faculty with respect to the value of retaining their copyrights and self-archiving their publications to help advance public access and open access scholarship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…These results clarify the findings of other studies that have found knowledge gaps and uncertainty in the health sciences regarding open access and scholarly communication, including those by: Spezi (2013), Charbonneau and McGlone (2013), Cullen andChawner (2011), Creaser et al (2010), Dawson (2014) , andFry et al (2009). The results reported here reveal significant disciplinary differences with regard to specific aspects and elements of the scholarly communication environment.…”
Section: A Knowledge Gap In the Health Sciencessupporting
confidence: 76%
See 1 more Smart Citation
“…These results clarify the findings of other studies that have found knowledge gaps and uncertainty in the health sciences regarding open access and scholarly communication, including those by: Spezi (2013), Charbonneau and McGlone (2013), Cullen andChawner (2011), Creaser et al (2010), Dawson (2014) , andFry et al (2009). The results reported here reveal significant disciplinary differences with regard to specific aspects and elements of the scholarly communication environment.…”
Section: A Knowledge Gap In the Health Sciencessupporting
confidence: 76%
“…Studies by Charbonneau and McGlone (2013), Smith et al (2006), and Kim (2010) have found a low degree of knowledge regarding copyright policies and authors' rights. Rather than focusing on respondents' understanding of copyright, we focused on what activities related to authors' rights our respondents would be willing to undertake (see Figure 1).…”
Section: Authors' Rightsmentioning
confidence: 99%
“…Some studies show that authors are likely unaware of both the idea of open access and the ways in which the publishing contracts they sign affect their copyrights. In one study, 90 percent of faculty say they sign their copyright contract with a publisher as-is, instead of trying to negotiate for friendly deposit rights (Charbonneau & McGlone, 2013). Another Malaysian study found that 70 percent of researchers said they knew what OA was but could not give a full and correct definition (Abrizah, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As journal policies could be confusing, difficult to follow, and unclear, faculty authors usually do not examine the copyright terms and sign it as is (Charbonneau & McGlone, 2013). There is no doubt that copyright restrictions imposed by publishers will remain a key barrier for libraries to make research output publicly accessible via institutional repositories.…”
Section: Common Challenges Facing Ir Content Recruitmentmentioning
confidence: 99%